Agency theory perspective on public-private-partnerships: international development project. Issue 2 (12th February 2018) - Parker, David W.; Dressel, Uwe; Chevers, Delroy; Zeppetella, Luca
Abstract : Purpose: Agency theory suggests that divergences will occur when a principal, e.g. client, and agent e.g. a project manager, interests are different in the execution of a project. The purpose of this paper is to explore if the agency theory can explain the subtleties integral to the behaviours and relationships between players delivering a public-private-partnership (PPP) in the context of an international development (ID) project. The intra-/interpersonal dynamics include governments, non-governmental organisations (NGOs) and private commercial service providers. The authors develop a conceptual framework and provide evidence from a case study of the testing of a Road Safety Toolkit in Kenya to explore several propositions. Design/methodology/approach: Extant literature identified application of the agency theory, and the development of a conceptual framework. A case study describing an ID project was used to validate the propositions prior to the expansion of a research instrument for data collection in the field. Findings: Through the lens of the agency theory and the limitations imposed by exploring a series of propositions, several insightful conclusions have been derived from the case. ID projects have particular nuisances that make them unique when compared to the majority of commercial applications. An added dimension and level of complexity is a consequence of the PPP incorporating government, NGOs and private corporations. The case exemplified the need for PPP ID projects to build on partner networks to influence and disseminate outcomes. Some agency problems were far less prominent than would normally be seen in a commercial project. Research limitations/implications: The methodologies presented in this paper need to be adapted and practiced in different kinds of ID projects in order to get confirmatory analytical results. The limitations imposed by the use of the single case, whilst drawing insightful conclusions, would necessitate greater testing in the field. Practical implications: Although the problems of the agency theory are well researched in the operations management literature, there is limited application to ID projects and no previous research within the context of a PPP. Therefore, this work is important for greater understanding of the specific issues associated with project delivery of an ID. Social implications: Conflicting goals between principals and agents are common for organisations, which in turn affect inter-relationships on an international footing. The agency theory has had little attention in the project management field, yet is fundamental to relationships and communication. Originality/value: There has been little research that explores the agency theory in the context of a PPP involving governments, NGOs and private commercial service providers, executed as an ID project. This work, therefore, exhibits new and novel findings.